2020
DOI: 10.1055/a-1149-9092
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Ultrasound Can Predict Endoscopic Activity in Crohn’s Disease

Abstract: Purpose To explore the ability of gastrointestinal ultrasound (GIUS) to separate patients in endoscopic remission from patients with active disease in a heterogeneous hospital cohort with Crohn’s disease (CD). Materials and Methods 145 CD patients scheduled for ileocolonoscopy were prospectively included. The endoscopic disease activity was quantified using the Simple Endoscopic Score for Crohn’s disease (SES-CD), and mucosal healing was strictly defined as SES-CD = 0. Ultrasound remission was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Other IUS findings can further change management decisions by identifying a more complicated course (such as fistula, abscess, or stenosis). Doppler measurements performed on pathologically thickened bowel walls should be considered for disease-activity quantification, supporting previous reports [ 3 , 4 ]. Furthermore, a recently published TRUST study showed improvement of IUS parameters after treatment, promising the usefulness of IUS as an alternative and fast imaging modality to determine transmural healing [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Other IUS findings can further change management decisions by identifying a more complicated course (such as fistula, abscess, or stenosis). Doppler measurements performed on pathologically thickened bowel walls should be considered for disease-activity quantification, supporting previous reports [ 3 , 4 ]. Furthermore, a recently published TRUST study showed improvement of IUS parameters after treatment, promising the usefulness of IUS as an alternative and fast imaging modality to determine transmural healing [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…The diagnostic capability of IUS examination was high, with a sensitivity of 94% and a specificity of 70.6%, which are in accordance with literature evaluating the performance of the ultrasonographic technique using conventional ultrasound systems in different clinical scenarios [ 2 ]. In a recent study using conventional high-tech ultrasound, Sævik et al [ 3 ] demonstrated that IUS achieved a sensitivity of 92.2% and a specificity of 86% in evaluating disease activity, in which mucosal healing was strictly defined as SES-CD = 0. Based on this high sensitivity, authors suggested that patients with active disease on IUS do not need an ileocolonoscopy as the false-positivity rate was low for IUS; however, patients with ileocolonic disease and normal findings on IUS should be examined using ileocolonoscopy to exclude false negativities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations